2010
DOI: 10.1021/ic1019873
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Tethered Ruthenium Nitrosyls Containing Planar Dicarboxamide Tetradentate N4 Ligands: Effects of In-Plane Ligand Twist on NO Photolability

Abstract: To examine the steric effects of the in-plane ligands in dye-sensitized {RuNO}(6) nitrosyls on their NO photolability, two new ligands, namely, 1,2-Bis(pyridine-2-carboxamido)-4,5-dimethoxybenzene (H(2)(OMe)(2)bpb) and 1,2-Bis(Isoquinoline-1-carboxamido)-4,5-dimethoxybenzene (H(2)(OMe)(2)IQ1, H's are dissociable carboxamide protons) have been designed and synthesized. The syntheses and spectroscopic properties of {RuNO}(6) nitrosyls derived from these two ligands, namely, [((OMe)(2)bpb)Ru(NO)(Cl)] (4-Cl), [((O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
1
32
1
Order By: Relevance
“…Φ NO was determined to be 0.19-0.34 depending on the solvents (Table 2). The observed Φ NO values of Ru-(EPBP)(NO)Cl are greater than those obtained from most of the previously reported mononuclear {RuNO} 6 complexes (SI, Table S3), [12,22,26,27,31,[46][47][48][49][50][51][52] and almost the highest among those of the nuetral {RuÀ NO} 6 complexes, indicating that the EPBP 2À ligand provides an effective platform forming RuNO complexes useful for NO-photoreleasing. The negatively charged and strong σ-donating EPBP 2À ligand might benifit the high quantum yields by both stabilizing the photoproducts and interfering with NO recombination.…”
Section: Photochemical Quantum Yieldcontrasting
confidence: 66%
See 1 more Smart Citation
“…Φ NO was determined to be 0.19-0.34 depending on the solvents (Table 2). The observed Φ NO values of Ru-(EPBP)(NO)Cl are greater than those obtained from most of the previously reported mononuclear {RuNO} 6 complexes (SI, Table S3), [12,22,26,27,31,[46][47][48][49][50][51][52] and almost the highest among those of the nuetral {RuÀ NO} 6 complexes, indicating that the EPBP 2À ligand provides an effective platform forming RuNO complexes useful for NO-photoreleasing. The negatively charged and strong σ-donating EPBP 2À ligand might benifit the high quantum yields by both stabilizing the photoproducts and interfering with NO recombination.…”
Section: Photochemical Quantum Yieldcontrasting
confidence: 66%
“…Those lengths are in accordance with the reported values found in the RuNO complexes with the {RuNO} 6 electron configurations. [7,[18][19][20][21][22][23][24][25][26][27][28][29] The arrangement of RuÀ NÀ O is close to linearity with the bond angle of 170.5(5)°. This bond angle and the observed NO stretching vibration (ν NO ) at 1850 cm À 1 (SI, Figure S1(A)) indicate that the electronic structure of the complex can be assigned to Ru(II)-(NO + ).…”
Section: Synthesis and Crystal Structure Of [Ru(epbp)cl(no)]c 2 H 5 Oh (1)mentioning
confidence: 71%
“…Previous studies of the photochemical behavior of the salen ruthenium nitrosyls [Ru(salen)(Cl)(NO)] and [Ru(salen)(NO)(H 2 O)] {H 2 ‐salen = N , N′ ‐bis(salicylaldehyde)ethylenediimine} revealed that the quantum yields for release of NO under UV light irradiation (355 nm) were small, and the compounds were eventually converted into the corresponding solvated products . Mascharak and co‐workers have systematically investigated the dicarboxamide tetradentate ligands with ruthenium nitrosyls for some years , .…”
Section: Ruthenium Nitrosyls (Ru‐nos) For No Releasementioning
confidence: 99%
“…Having more carboxamide groups resulted in a higher bathochromic effect, higher quantum yields, and a better stability under physiological conditions [90,107,108]. An example is the tetradentate anionic ligand bpb -containing two carboxamide groups (H 2 bpb = 1,2-bis(pyridine-2-carboxamido)benzene) from which they prepared the ruthenium complexes Ru(bpb)(NO)(X) Interestingly, the more sterically crowded Ru((OMe) 2 bQb)(NO)(Cl) (Figure 11) is less photoactive than the isoquinoline analog Ru((OMe) 2 IQ1)(NO)(Cl) [32] …”
Section: Ruthenium Complexesmentioning
confidence: 99%